Operações urbanas em Belo Horizonte e a proposta das operações urbanas consorciadas: Nova BH, Antônio Carlos/Pedro I – Leste-Oeste (ACLO) à OUC Centro-Lagoinha - Lara Figueiredo Peres Pessl (2023)
The work to analyze aims at the situation of Lagoinha, a neighborhood located in the Northwest region of Belo Horizonte in Brazil, through the proposals of the consortium urban operation Nova BH, Antônio Carlos/Pedro I – Leste-Oeste (ACLO) and the Centro-Lagoinha Qualification Plan, the most recent proposal for an urban operation in Belo Horizonte. This instrument of flexibility of urban parameters based on Public-Private Partnerships (PPPs) has taken precedence over other planning instruments and has resulted in the supremacy of private interests to the detriment of collective interests. The OUC appears in a context of critical reproduction of capital, neoliberalism and urban entrepreneurship. The current neoliberal urban policy, supported by the hegemony of the logic of profitability and financialization, influences the competition between cities in the search for capital in transmission processes. It also seeks to investigate the historically instituted power disputes in the Lagoinha region, from what happened in the neighborhood to the present day, where successive investments in urban mobility works have been made, privileging the automobile, until recent urban requalification works, in an attempt to repair the historical process of large urban projects (GPUs) that marked the complex of viaducts that cross the neighborhood, where one can observe an overlapping of lines of forces that are reconfigured in the landscape of the neighborhood, in addition to identifying the human and non-human actors involved in this process, especially with regard to gentrification linked to the concept of urban protection linked to the encouragement of "re" phenomena and processes: requalifications, restructuring, recompositions, renovation, rehabilitation, reurbanization supported by public-private partnerships (PPPs) . There is a territorial dispute due to its strategic location in the region, where it is intended to investigate the neoliberal reason embedded in this process (DARDOT; LAVAL, 2016) that are reconfigured due to the new tactics of biopolitical control (FOUCAULT, 2008). The work methodology is based on the Cartographic Method developed by the UFMG Indisciplinary research group (LOPES; RENA; SÁ, 2019) whose theoretical structure is based on the concept of rhizome (DELEUZE; GUATTARI, 1996) and actor-network theory (LATOUR, 2012), to understand the genealogy of power, aiming to connect control points capable of disrupting the hegemonic rationality. The research has an interdisciplinary character and proposes a historiographical process of the region linked to the genealogical character (FOUCAULT, 2017) in order to identify events, narratives, controversies and actors in the region.